Jewish hermeneutics of divine testing with special reference to the epistle of James - Ellis, N (2013)
The nature of trials, tests, and temptation in the Epistle of James has been extensively debated in New Testament scholarship. However, scholarship has underexamined the tension between the author’s mitigation of divine agency in testing ( Jas 1:13–14) and the author’s appeal to well-known biblical testing narratives such as the creation account (1:15– 18), the Binding of Isaac ( Jas 2:21–24), and the Trials of Job ( Jas 5:9–11). This juxtaposition between the author’s theological apologetic and his biblical hermeneutic has the potential to reveal either the author’s theological incoherence or his rhetorical and hermeneutical creativity. With these tensions of divine agency and biblical interpretation in mind, this dissertation compares the Epistle of James against other examples of ancient Jewish interpretation, interrogating two points of contact in each Jewish work: their portrayals of the cosmic drama of testing, and their resulting biblical hermeneutic. The dissertation assembles a spectrum of positions on how the divine, satanic, and human roles of testing vary from author to author. These variations of the dramatis personae of the cosmic drama exercise a direct influence on the reception and interpretation of the biblical testing narratives. When the Epistle of James is examined in a similar light, it reveals a cosmic drama especially dependent on the metaphor of the divine law court. Within this cosmic drama, God stands as righteous judge, and in the place of divine prosecutor stand the cosmic forces indicting both divine integrity and human religious loyalty. These cosmic and human roles have a direct impact on James’ reading of biblical testing narratives. Utilising an intra-canonical hermeneutic similar to that found in Rewritten Bible literature, the Epistle appeals to a constructed ‘Jobraham’ narrative in which the Job stories mitigate divine agency in biblical trials such as those of Abraham, and Abraham’s celebrated patience rehabilitates Job’s rebellious response to trial. In conclusion, by closely examining the broader exegetical discourses of ancient Judaism, this project sheds new light on how the Epistle of James responds to theological tensions within its religious community through a hermeneutical application of the dominant biblical narratives of Job’s cosmic framework and Abraham’s human perfection.